The impact of employee engagement program in reducing absenteeism at workplace: A case of government-linked company (GLC) in Malaysia - Othman, Sarimah; Romle, Abd Rahim; Mohamad Idris, Abd. Manaf (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
Employee engagements program plays important roles in the employer and employees relationship. The effective engagement programs will contribute to increase the attendance rates and reduce absenteeism in most organization.Furthermore, sense of belonging can drive employees to perform their daily routine tasks in conducive environment.In most cases, effective engagement programs will give indirect impact to the organization performance.